Study of Pond Waste in Sarjo Village Waters District Sarjo, Pasangkayu Regency - Hidayatullah; Saputra , Iwan Alim; Ya'la , Zakira Raihani; Maliki , Rendra Zainal; Widyastuti; Risma Fadhilia Arsy (Tadulako Social Science and Humaniora Journal, 2021)
The problem in this research is the quality of the water in the waters around the Sarjo Village pond and the impact of pond waste on the environment around the Sarjo Village pond. The objectives to be achieved are (1) Assessing the water quality conditions around the Sarjo Village pond. (2) Analyze the impact of waste around the Sarjo Village pond. The type of research used is descriptive quantitative with an ecological approach. The sample used is pond wastewater. The techniques used are interview techniques, observation, and documentation. Data analysis in this research is a comparative technique. The results achieved in this research are (1) water quality that still meets quality standards, namely: temperature, brightness, pH, TSS, TDS, ammonia, phosphate, and salinity. The parameters in the waters around the ponds that do not comply with quality standards are Color and Odor at station 1 and station 2 and Nitrate at the 3 stations. (2) Based on the results of data analysis on the impact of pond waste from the nitrate content at the 3 stations which exceeds the threshold, this certainly has an impact on aquatic productivity, because it affects the biota or fish in the surrounding waters because high nitrate content can reduce oxygen levels in the water and anticipate eutrophication. Inappropriate brightness and odor at stations 1 and 2 and the brownish-black color can inhibit lighting in the waters which can inhibit the process of photosynthesis in the waters. Based on the results of calculating the pollution index (Pi), the diversity index (H'), the uniformity index (E), and the dominance index (C), these four indices show the appropriate results that the Sarjo Village pond waste disposal waters have the status of "Slightly/Moderately polluted ".